Innovation in Islamic Education Curriculum Based on Religious Moderation in a Multicultural Society - Syahrudin Syahrudin; Aan Gunawan (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Innovation in the Islamic education curriculum is essential to respond to the challenges of a multicultural society characterized by religious, ethnic, and cultural diversity. This study aims to analyze the concept, forms, and implications of curriculum innovation in Islamic education based on the values of religious moderation. Using a qualitative approach through literature review and conceptual analysis, this research explores how principles of religious moderation such as tolerance, balance (tawassuth), justice (‘adl), and respect for diversity can be systematically integrated into curriculum objectives, learning materials, teaching strategies, and assessment systems. The findings indicate that curriculum innovation grounded in religious moderation contributes to strengthening inclusive religious understanding, preventing extremism, and fostering harmonious social relations among learners in multicultural settings. Furthermore, the integration of local wisdom, contextual learning, and dialogical pedagogical approaches enhances students’ critical thinking, empathy, and civic responsibility. This study concludes that a religious moderation-based Islamic education curriculum serves as a strategic framework for nurturing moderate, open-minded, and socially responsible Muslim generations capable of living peacefully in a pluralistic society.